2023
DOI: 10.1038/s41419-023-05860-7
|View full text |Cite
|
Sign up to set email alerts
|

SLC43A2 and NFκB signaling pathway regulate methionine/cystine restriction-induced ferroptosis in esophageal squamous cell carcinoma via a feedback loop

Abstract: Studies have indicated dietary restriction of methionine/cystine provided a therapeutic benefit in diseases such as cancer. However, the molecular and cellular mechanisms that underlie the interaction between methionine/cystine restriction (MCR) and effects on esophageal squamous cell carcinoma (ESCC) have remained elusive. Here, we discovered the dietary restriction of methionine/cystine has a large effect on cellular methionine metabolism as assayed in a ECA109 derived xenograft model. RNA-seq and enrichment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 68 publications
0
3
0
Order By: Relevance
“…Importantly, SLC43A2 increases the phosphorylation of IKKα/β and p65, and NF-κB silencing leads to inhibition of SLC43A2 and GPX4 in both mRNA and protein levels, thereby downregulation of methionine uptake. Following these changes, ferroptosis and apoptosis are induced and esophageal squamous cell carcinoma progression is impaired [ 215 ]. In a novel study, CRISPR/Cas9 system carrying in nanoplatforms was used to decrease methionine intake by cancer cells via inhibiting SLC43A2.…”
Section: Slcs In Cancermentioning
confidence: 99%
“…Importantly, SLC43A2 increases the phosphorylation of IKKα/β and p65, and NF-κB silencing leads to inhibition of SLC43A2 and GPX4 in both mRNA and protein levels, thereby downregulation of methionine uptake. Following these changes, ferroptosis and apoptosis are induced and esophageal squamous cell carcinoma progression is impaired [ 215 ]. In a novel study, CRISPR/Cas9 system carrying in nanoplatforms was used to decrease methionine intake by cancer cells via inhibiting SLC43A2.…”
Section: Slcs In Cancermentioning
confidence: 99%
“…Chemotherapy is the main treatment method for ESCA, and resistance to chemotherapeutic drugs is an important obstacle to effective treatment. However, HMGA1 can drive chemotherapy resistance in ESCA by inhibiting ferroptosis [3]. Extracellular vesicles (EVs) are small extracellular vesicles.…”
Section: Introductionmentioning
confidence: 99%
“…Due to the high proliferative rate, cancer cells mainly depend on the methionine cycle for methylation reaction as well as the production of H 2 S and GSH [ 10 ]. A study found that cancer cells express high levels of methionine transporter SLC43A2 for the consumption of more methionine, which causes cancer progression [ 11 ]. Many studies found that a methionine restriction diet can reduce cancer risk and progression through various molecular processes [ 10 , 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%